2016
DOI: 10.1038/onc.2016.170
|View full text |Cite
|
Sign up to set email alerts
|

Integrated genomic analysis of colorectal cancer progression reveals activation of EGFR through demethylation of the EREG promoter

Abstract: Key molecular drivers that underlie transformation of colonic epithelium into colorectal adenocarcinoma (CRC) are well described. However, the mechanisms through which clinically targeted pathways are activated during CRC progression have yet to be elucidated. Here, we used an integrative genomics approach to examine CRC progression. We used laser capture microdissection to isolate colonic crypt cells, differentiated surface epithelium, adenomas, carcinomas and metastases, and used gene expression profiling to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(59 citation statements)
references
References 56 publications
3
56
0
Order By: Relevance
“…Overexpression of GNG4 inhibits cell growth of glioblastoma cell lines and in vitro transformation of immortalized human astrocytes, hence indicating a probable tumor suppressor character of GNG4 in glioblastoma [38]. Palma P et al identified increased GNG4 expression level in treatment-responsive rectal cancer samples compared with nonresponsive rectal tumor patients [30]. Our results reveled that GNG4 is highly expressed in the left-side colon.…”
Section: Cellular Physiology and Biochemistrysupporting
confidence: 64%
See 1 more Smart Citation
“…Overexpression of GNG4 inhibits cell growth of glioblastoma cell lines and in vitro transformation of immortalized human astrocytes, hence indicating a probable tumor suppressor character of GNG4 in glioblastoma [38]. Palma P et al identified increased GNG4 expression level in treatment-responsive rectal cancer samples compared with nonresponsive rectal tumor patients [30]. Our results reveled that GNG4 is highly expressed in the left-side colon.…”
Section: Cellular Physiology and Biochemistrysupporting
confidence: 64%
“…Qu X et al found that in those patients treated with cetuximab, low EREG methylation was correlated with increased expression of the ligand of EREG, also was related to a better response to the cetuximab treatment. On the contrary, high EREG methylation was correlated with decreased expression of the ligand of EREG, as well as was related to the worse response of therapy [30]. Lee MS et al found that there were noteworthy inverse correlations between EREG expression and methylation, as well as tumor position, BRAF mutation, and CIMP-high status [31].…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 99%
“…To ensure consistency of data processing, we only compared our samples with publically accessible samples with raw idat files. GSE68060, GSE68838, GSE77954, GSE77965, GSE81211, GSE101764, GSE107352, and GSE75546 were collected from GEO while E-MTAB-6450 was collected from ArrayExpress [43][44][45][46][47][48] (Additional file 1: Table S6). Some cell line samples and metastatic cancer samples were removed upon further study.…”
Section: Public Datasets and Processingmentioning
confidence: 99%
“…The expression of ErbB-1, -2 and -4 tends to be higher in the ileum than in other areas of the intestines tract [10]. Qu et al reported that epiregulin expression is confined to epithelial cells in the colon [6]. These findings suggest that the intensity of immunostaining in the intestines is proportional to ErbB family expression in the intestines.…”
Section: Resultsmentioning
confidence: 99%